An approximate solitary wave solution with compact support for the modified KdV equation - İnç, Mustafa (Elsevier Science Inc, 2007)
We implemented a variational method for approximate solution of the modified KdV equation. By using this scheme, the explicit exact solution is calculated in the form of a quickly convergent series with easily computable components. To illustrate the application of this method, numerical results are derived by using the calculated components of the variational series. The obtained results are found to be in good agreement with the exact solution. (C) 2006 Elsevier Inc. All rights reserved.
Keywords: modified KdV equation; variational iteration method; Lagrange multiplier